ANALISIS POLA KONSUMSI PANGAN MINYAK DAN KELAPA RUMAH TANGGA DI PROVINSI RIAU - Novita Dewi Limbong; Djaimi Bakce; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Oil and coconut are food sources of fat that can produce energy that the body needs to carry out activities or activities. Oil and coconut food consumption in Riau Province is dominated by cooking oil commodity. This study aims to analyze the pattern of household consumption of oil and coconut based on income, number of household members and education of housewives in Riau Province. The data used in this research is secondary data obtained from the results of the National Socio-Economic Survey (SUSENAS) for the province of Riau in 2018 issued by the Central Statistics Agency. This research uses quantitative descriptive analysis. The results showed that the calorie consumption of food oil and coconut in Riau Province in 2018 had exceeded the recommended energy consumption figure set by the National Food and Nutrition Widyakarya (WNPG) XI in 2018. The pattern of food consumption of oil and coconut in Riau Province is as follows: The higher the income, the share of expenditure for commodities of coconut oil, cooking oil and other oils and coconuts is increasing. The more the number of household members, the lower the share of expenditure for cooking oil and other oil and coconut commodities. The higher the education of housewives, the higher the share of expenditure for cooking oil and other oil and coconut commodities. Keywords: oil and coconut food consumption, food consumption patterns